2001
DOI: 10.1074/jbc.m101406200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-γ Mediates the Hydrolysis of Phosphatidylinositol, but Not of Phosphatidylinositol 4,5-Bisphoshate, in Carbamylcholine-stimulated Islets of Langerhans

Abstract: In pancreatic islets the activation of phospholipase C (PLC) by the muscarinic receptor agonist carbamyolcholine (carbachol) results in the hydrolysis of both phosphatidylinositol 4,5-bisphosphate (PtdInsP 2 ) and phosphatidylinositol (PtdIns). Here we tested the hypothesis that PtdIns hydrolysis is mediated by PLC␥1, which is known to be regulated by activation of tyrosine kinases and PtdIns 3-kinase. PtdIns breakdown was more sensitive than that of PtdInsP 2 to the tyrosine kinase inhibitor, genistein. Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…It is possible that the large excess of PLC-␤ 3 relative to PLC-␤ 1 in Ad-PLC-␤ 3 NCM competes for access to endogenous G␣ q (13). Overexpression of PLC-␥ 1 (27) did not alter [ 3 H]InsP responses to either NE or ATP, and the tyrosine kinase inhibitor genistein (50 M) was not inhibitory (data not shown). Thus, neither receptor appears to be coupled to PLC-␥ under the conditions of our experiments (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the large excess of PLC-␤ 3 relative to PLC-␤ 1 in Ad-PLC-␤ 3 NCM competes for access to endogenous G␣ q (13). Overexpression of PLC-␥ 1 (27) did not alter [ 3 H]InsP responses to either NE or ATP, and the tyrosine kinase inhibitor genistein (50 M) was not inhibitory (data not shown). Thus, neither receptor appears to be coupled to PLC-␥ under the conditions of our experiments (35).…”
Section: Discussionmentioning
confidence: 99%
“…Blank virus (Ad-MX) contained the adenoviral backbone but expressed no additional gene product. Rat PLC␥ 1 was subcloned into pShuttle-CMV and recombined with pAdEasy-1 (27).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, depolarization was reported to inhibit PLC-mediated hydrolysis of phosphatidylinositol without effect on PIP 2 in rat islets (29). The different regulation of phosphatidylinositol and PIP 2 hydrolysis may reflect the involvement of different PLC isoforms with distinct substrate specificities (30 . Although the phenomenon still remains to be shown in primary ␤-cells, we have observed oscillations in PLC activity also in murine insulin-secreting MIN6 cells, which exhibit a glucose sensitivity similar to that of primary ␤-cells.…”
Section: Depolarization and Elevation Of [Ca 2ϩ ] I Activate Plc In Imentioning
confidence: 91%
“…The eukaryotic PI-PLCs can use PtdIns, PtdIns4P, and PtdIns(4,5)P 2 but not 3-phosphorylated inositides as substrates in vitro, but they are believed to act primarily on PtdIns(4,5)P 2 in their native cellular environment. Only a few studies addressed this question rigorously, and a few reports suggested that PLCs act on PtdIns (1066) and that they are present in intracellular locations (149,354), where they could act on PtdIns or PtdIns4P.…”
Section: Phospholipase C Enzymesmentioning
confidence: 99%